An assessment of tools for UML class diagram modeling: support to adaptation and integration with other tools - Massago, Mamoru; Colanzi, Thelma Elita (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2019)
The software development process comprises a set of activities with the goal of developing high quality software. The software architecture design is a key activity of the software development processs as it allows the specification and visualization of products from different and structured point of views. One of the most used architectural views is the logical one, which represents the classes and their relationships. For this reason, the UML class diagram is one of the most used UML diagrams by software engineers [1]. Many companies use CASE (Computer-Aided Software Engineering) tools to carry out several software engineering activities, including modeling class diagrams. They are looking for independence and flexibility to adapt and integrate tools through the adoption of open-source tools, but this is not an easy task as there are a lot of CASE tools and most of them are incompatible. This problem arises when it is necessary to integrate tools to perform software engineering activity that needs to receive a UML class diagram as input. In this sense, the objective of this work is to assist software engineers in the selection of the tools by presenting results of a systematic review, whose goal was identifying existing free and open-source tools for UML class diagram modeling and analyzing their support to adaptation and integration with other tools. Twelve tools for UML class diagrams modeling were found and an analysis of their support to adaptation and integration with other tools was carried out. This analysis is useful in the choice and use of such kind of tool, either in industry or academic research.